2015
DOI: 10.3109/17435390.2015.1090028
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies toxicity test for silver nanoparticles to derive hazardous concentration based on species sensitivity distribution for the protection of aquatic ecosystems

Abstract: With increasing concerns about the release of silver nanoparticles (AgNPs) into the environment and the risks they pose to ecological and human health, a number of studies of AgNP toxicity to aquatic organisms have been conducted. USEPA and EU JRC have published risk assessment reports for AgNPs. However, most previous studies have focused on the adverse effects of AgNPs on individual species. Hazardous concentration (HC) of AgNPs for protection of aquatic ecosystems that are based on species sensitivity distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
3
19
2
Order By: Relevance
“…Silver NPs are used in a wide variety of products including medical and personal care products, food containers, textiles, paints, and disinfectants (Reidy et al 2013;Keller et al 2014;Caballero-Guzman and Nowack 2016;Mackevica et al 2016;McClements and Xiao 2017). Migration of AgNPs from these products into the aquatic environment after use may pose toxicity risks to organisms (Matzke et al 2014;Kwak et al 2016). However, their impacts on ecosystems and human health are not fully evaluated (Kwok et al 2016;Selck et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Silver NPs are used in a wide variety of products including medical and personal care products, food containers, textiles, paints, and disinfectants (Reidy et al 2013;Keller et al 2014;Caballero-Guzman and Nowack 2016;Mackevica et al 2016;McClements and Xiao 2017). Migration of AgNPs from these products into the aquatic environment after use may pose toxicity risks to organisms (Matzke et al 2014;Kwak et al 2016). However, their impacts on ecosystems and human health are not fully evaluated (Kwok et al 2016;Selck et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are several methodologies which are employed by regulatory bodies in different countries to derive HC 5 values and we chose the species sensitivity distribution (SSD) approach. Since we only had acute toxicity test results, the USEPA protocol was adopted since it supports using acute toxicity values (Kwak et al, 2016). To predict more accurate HC 5 values, toxicity values of sufficient species should be available representing a comprehensive ecosystem.…”
Section: Hazardous Concentration (Hc) Of Coated Agnps and Ag + Ionsmentioning
confidence: 99%
“…Besides, there is no commensurate investment in environmental safety research while we invest heavily in the development of new nanotechnologies (Miller and Wickson, 2015). There are several known and unknown hurdles in evaluating the toxicity of NPs (Fabrega et al, 2011;Kumar et al, 2017) and the reported recommendation values for the protection of aquatic species in the literature vary greatly (USEPA, 1985(USEPA, , 2012Fabrega et al, 2011;Gubbins et al, 2011;CCME, 2015;Kwak et al, 2016). Multispecies toxicity studies which include different trophic levels or species with different life strategies are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations